On A. Smith, A. Meinong, and Contemplative Altruism - Norkus, Zenonas (Problemos, 1994)
Theory of moral value of Austrian philosopher A. Meinong (1853-1920) is considered as an intermediating link between British empiricist ethics and analytical ethics. It is shown that as A. Smith’s “Theory of Moral Sentiments” is a counterpart to his economic theory, so A. Meinong’s theory of moral value is a counterpart to economic theories of “Old Austrian school” (C. Menger, F. Wieser, E. Boehm-Bawerk). Finally, the distinction between contemplative and active altruism is made, and the outline of the theory of moral value of contemplative altruism is derived.